1981
DOI: 10.1139/f81-042
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an Adaptive Basis for Geographic Variation in Body Morphology and Time of Downstream Migration of Juvenile Atlantic Salmon (Salmo salar)

Abstract: Differences in growth rate, proximate composition, body morphology, and time of downstream migration between two populations inhabiting tributaries of the Miramichi River, New Brunswick, that differed in distance from the head of tide, temperature, and flow velocity were studied. Rocky Brook, located 132.6 km above the head of tide, had lower temperatures and higher average flow velocities than Sabbies River, located 42.5 km above tide. Growth rate and proximate composition were similar between populations, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(114 citation statements)
references
References 19 publications
4
108
2
Order By: Relevance
“…Morphologically, fish from fast versus slow flowing water conform to hydromechanical predictions (fast-water fish have shallower bodies and caudal peduncles); however, these differences have not been correlated with locomotor performance (e.g., Gatz 1979;Riddell and Leggett 1981;McLaughlin and Grant 1994;Sagnes et al 1997).…”
mentioning
confidence: 73%
“…Morphologically, fish from fast versus slow flowing water conform to hydromechanical predictions (fast-water fish have shallower bodies and caudal peduncles); however, these differences have not been correlated with locomotor performance (e.g., Gatz 1979;Riddell and Leggett 1981;McLaughlin and Grant 1994;Sagnes et al 1997).…”
mentioning
confidence: 73%
“…Furthermore, the physiological consequences of acclimatization to fluctuating (but rapidly declining) water temperatures have been shown to be very taxing on the energy reserves of stream salmonids (Cunjak et al, 1987;Cunjak and Power, 1987b;Cunjak, 1988b). The emergence of such energetically demanding conditions has been observed to cause considerable fish loss (Riddell and Leggett, 1981;Smith and Griffith, 1994;Finstad et al, 2004) and may have also contributed to the observed parr emigration in the Øyvollen reach in autumn.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases the variation has been observed among populations from rearing habitats differing in current speed (e .g . Riddell & Leggett 1981, Swain & Holtby 1989 . In others it has been observed among populations differing in the migration distance between their rearing streams and the sea (e.g .…”
Section: Introductionmentioning
confidence: 99%